Factors of health in the protection against death and cardiovascular disease among adults with subclinical atherosclerosis - Al Rifai, Mahmoud; Greenland, Philip; Blaha, Michael J.; Michos, Erin D.; Nasir, Khurram; Miedema, Michael D.; Yeboah, Joseph; Sandfort, Veit; Frazier-Wood, Alexis C.; Shea, Steven; Lima, Joao AC; Szklo, Moyses; et al. (The American heart journal, 2018)
Although cardiovascular disease (CVD) prevention traditionally emphasizes risk factor control, recent evidence also supports the promotion of “health factors” associated with cardiovascular wellness. However, whether such health factors exist among adults with advanced subclinical atherosclerosis is unknown. We aimed to study the association between health factors and events among persons with elevated coronary artery calcium (CAC). Self-reported health-factors studied included nonsmoking, physical activity, Mediterranean-style diet, sleep quality, emotional support, low stress burden, and absence of depression. Measured health-factors included optimal weight, blood pressure, lipids, and glucose. Multivariable-adjusted Cox models examined the association between health factors and incident CVD or mortality, independent of risk factor treatment. Accelerated failure time models assessed whether health factors were associated with relative time delays in disease onset. Among 1,601 Multi-Ethnic Study of Atherosclerosis participants with CAC >100 without baseline clinical atherosclerotic CVD, mean age was 69 (±9) years, 64% were male, and median CAC score was 332 Agatston units. Over 12 years of follow-up, nonsmoking, high-density lipoprotein cholesterol levels >40 mg/dL for men and >50 mg/dL for women, and low stress burden were inversely associated with ASCVD (hazard ratios ranging from 0.58 to 0.71, all P<.05). Nonsmoking, glucose levels <100 mg/dL, regular physical activity, and low stress burden were inversely associated with mortality (hazard ratios ranging from 0.40 to 0.77, all P<.05). Each of these factors was also associated with delays in onset of clinical disease, as was absence of depression. Adults with elevated CAC appear to have healthy lifestyle options to lower risk and delay onset of CVD, over and above standard preventive therapies.